2019
DOI: 10.2105/ajph.2019.305211
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Women and Contraceptive Use: Complex Pathways Between Sexual Orientation and Health Outcomes

Abstract: Compared with their heterosexual peers, sexual minority women (SMW; e.g., queer, bisexual, lesbian, pansexual) have an elevated risk for unintended pregnancy. A team of social science and clinical researchers qualitatively documented the multilevel pathways leading to this disparity, particularly the contexts of contraceptive use. From August 2017 to April 2018, we conducted focus groups and interviews with young adult cisgender SMW in 3 cities: Chicago, Illinois; Madison, Wisconsin; and Salt Lake City, Utah.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…18,19 Bisexual women may face stereotyping related to the idea that they are promiscuous or that their identity is not valid, and this stereotyping may compound their experiences of stigma. [20][21][22] Prior research has demonstrated that diverse groups of SMW face fear of stigmatization from health care providers 23 and that bisexual women may face unique burdens in health care settings, such as invisibility and misunderstanding from health care providers. 24 It should be highlighted that most low efficacy methods of birth control are available over the counter or do not require any interaction with a health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Bisexual women may face stereotyping related to the idea that they are promiscuous or that their identity is not valid, and this stereotyping may compound their experiences of stigma. [20][21][22] Prior research has demonstrated that diverse groups of SMW face fear of stigmatization from health care providers 23 and that bisexual women may face unique burdens in health care settings, such as invisibility and misunderstanding from health care providers. 24 It should be highlighted that most low efficacy methods of birth control are available over the counter or do not require any interaction with a health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…SMW's risks for unintended pregnancy may be further heightened by decreased use of contraception and lower provision of contraceptive counseling (Charlton et al, ; Everett, Higgins, Haider, & Carpenter, ). SMW may perceive that they do not need regular contraception if sexual intercourse with men is a relatively rare event and may be reluctant to seek contraception because of the stigma against contraceptive use within some queer communities (Higgins et al, ). SMW are also more likely to experience childhood and adulthood sexual abuse and victimization (Everett, ; Friedman et al, ; Katz‐Wise & Hyde, ; Xu et al, ), both of which have been linked to sexual risk‐taking behaviors and unintended pregnancy (Boyer & Fine, ; Dietz et al, ; Magnusson & Trost, ).…”
Section: Sexual Orientation Disparities In Unintended Pregnancymentioning
confidence: 99%
“…Race/ethnicity may also interact with sexual orientation to shape contraceptive use. For example, qualitative research based on a White‐majority sample of SMW identified several unique barriers to preventing unintended pregnancy (Higgins et al, ), such as fear of antigay stigma from health care providers, fear of anticontraception stigma within the queer community, resistance to identity as a regular contraceptive user, and the perception that one's risk for pregnancy was low if penile–vaginal intercourse was infrequent. Altogether, these factors provided robust disincentives to use contraceptives and regular contraceptive care.…”
Section: Sexual Orientation Disparities In Unintended Pregnancymentioning
confidence: 99%
“…For example, a presurvey provided at a Utah contraceptive training conference found that 65% of respondents (n=29) perceived that intrauterine placements were less uncomfortable for recipients if provided during menstruation [ 28 ]. In addition, research on sexual minority women in Utah found that these individuals are less likely to report having had a provider offer contraception or discuss pregnancy intentions or reproductive life planning [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%